2021
DOI: 10.1093/milmed/usab463
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis in a U.S. Army Basic Trainee

Abstract: Lymphocutaneous sporotrichosis is a mycotic disease caused by traumatic inoculation of the dimorphic fungus Sporothrix schenckii, found ubiquitously in decaying vegetation. The potential for outbreaks, difficulty with timely diagnosis, as well as the prolonged treatment course and recovery from surgical intervention can have a substantial impact on the medical readiness of service members. Treatment with the antifungal therapy of choice, itraconazole, requires close patient monitoring for the duration of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A total of 48 publications related to sporotrichosis were found in North America [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. There were 1460 patients in total associated with infection caused by species of the genus Sporothrix .…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 48 publications related to sporotrichosis were found in North America [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. There were 1460 patients in total associated with infection caused by species of the genus Sporothrix .…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
“…According to the previous classification, it was found that in Canada, only two case reports were found, one from Ontario and the other from Toronto [ 5 , 6 ]. In the US, 27 reports containing 1 clinical case were found (81.5% S. schenckii , 18.5% Sporothrix spp., S. schenckii complex, and S. schenckii sensu lato ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Of these, seven cases came from California, three from Oklahoma, two cases from Kansas, Texas, Arizona, Minnesota, and Florida, one case from Michigan, Nebraska, Oregon, Pennsylvania, and finally, one case without a specific city or region.…”
Section: Epidemiology Of Sporotrichosis In North Americamentioning
confidence: 99%
See 3 more Smart Citations